Respostas

2013-05-29T17:30:01-03:00

2x²- 8x=0 (incompleta)

x(2x-8)

x=0 ou 

2x-8=0                           S={0,4}

2x=8

x=8/2

x=4

 

m²+9=4m

m²-4m+9=0

a=1

b=-4

c=9

delta=(-4)²-4.1.9

delta=16-36

delta=-20 (equação não tem raízes reais, delta=negativo)

 

3y²-7y+2=0 

a=3

b=-7

c=2

delta=(-7)²-4.3.2                                                                          S={1/3, 2}

delta=49-24

delta=25

\frac{-(-7)+-\sqrt{25}}{2.3}\frac{7+-5}{6}

x1=2/6=1/3

x2=12/6=2

 

4+n(n-4)=n

4+n²-4n-n

n²-5n+4=0

a=1

b=-5                                                                                 S={1,4}

c=4

delta=(-5)²-4.1.4

delta=25-16

delta=9

x=\frac{-(-5)+-\sqrt{9}}{2.1} = \frac{5+-3}{2}

x1=2/2=1

x2=8/2=4

2 5 2